Historical perspectives : from the hasmoneans to bar kokhba in light of the dead sea scrolls. (Studies on the Texts of the Desert of Judah, 2001)
The papers published in this volume were presented at the Fourth Orion International Symposium (Jerusalem, 1999), whose focus was Jewish history in light of the Dead Sea Scrolls. The first section, "History of the Jews and Judaism," is devoted to specific topics in Jewish history, such as historical references in the Scrolls, comparative studies between the Scrolls and Josephus, and issues of Jewish nationalism. The second section, "Community and Covenant," comprises studies of community, Jewish law, and the concept of covenant. The third section, "Natural Sciences and the Scrolls," reports on examinations of DNA preserved in leather used for the Scrolls, of dust found in jars from Qumran, of the nature of the stitching of the Scrolls, and of the composition of the pottery found at Qumran.